Partnerships Between Sugarcane Factories and Farmers: Performance, Waste Management, and Perception Analysis - Sahara, Dewi; Dewi, Triyani; Handayani, Cicik Oktasari; Zu'amah, Hidayatuz; Arianti, Forita Dyah (Agro Ekonomi, 2025)
Sugarcane plays a crucial role in sugar production, but its supply has declined due to land conversion and inefficient systems, which has led to reduced sugar output. Partnerships between farmers and sugar factories are a strategic alternative to increase productivity. This study aims to evaluate sugar factories’ performance, sugarcane waste management, the partnership system with farmers, and farmers' perceptions of the impact of partnerships on the production system and the socioeconomics impact on the community. This research was conducted at three sugar factories  in Indonesia (Madukismo, Trangkil, and Mojo Sugar Factories) from March to September 2024. The methods used in this study include in-depth interviews, observations, and surveys. The data were analyzed using descriptive and scoring methods. The results showed that sugar factories produce white crystal sugar, distribute it to retail stores, and sell it to wholesalers through an open auction system. Some sugarcane waste is utilized as fuel for factories and processed into alcohol. The partnership between sugarcane farmers and sugar factories provides mutual benefits in which farmers receive guidance in the production process and access to business capital banking. In contrast, sugar factories receive adequate sugarcane supplies in quantity and quality. Farmers positively perceive the sugarcane production system and its socio-economic impact on the community through this partnership. Farmers' perceptions are a supporting factor for the sustainability of partnerships between sugarcane farmers and sugar factories. Policy implications emphasize the importance of factory management in building sustainable partnerships through fair contracts, technical support, access to capital, and environmentally friendly waste management innovations.